Knowledge and practice of Mothers of under Two Years Children On Complementary Feeding At Bharatpur Hospital, Chitwan, Nepal - Paudel, Radha Kumari; Basaula, Yuba Nidhi; Tiwari, Sunita (Journal of Advanced Academic Research, 2018)
Inappropriate complementary feeding practice is one of the main reasons for malnutrition among Nepal children aged less than two years. Exclusive breastfeeding for the first six months followed by complementary feeding along with breastfeeding is vital for proper growth and development of a child. This study was carried out to assess the knowledge and practices of mothers regarding complementary feeding, and to determine the factors influencing the inappropriateness of complementary feeding. A hospital based cross-sectional study was carried out at Bharatpur Hospital Chitwan, Nepal, involving mothers of children from 6 to 24 months of age who attended outpatient department of this hospital, using systematic sampling technique and applying semi-structured questionnaire. About 73.8 % of mothers knew they had to start breast feeding within ½-1 hours after birth. It was found in this study that around 20.8% mothers practiced exclusive breast feeding more than six months. Study shows that 52.30% mothers had introduced complementary feeds within six months. This study found that 50% mother fed their children appropriate complementary feeding. About26.1% mothers were found to be practicing ideal feeding in this study. It was observed in the study that 73.8% mothers had knowledge about the exclusive breast feeding. Most mothers (18.4%) knew when to start complementary feeding . Study shows that 52.30% mothers had introduced complementary feed within six month. Half of the mothers fed their child appropriate complementary feeding there was a knowledge and practice gap of duration of exclusive breast feeding and initiation and continuation of complementary feeding.